High temperature Au-based solder reliability in electronic packages for harsh environments - Sousa, M; Riches, S; Johnston, C; Grant, P (2011)
The operation of electronic packages in high temperature environments is a significant challenge for the microelectronics industry, and poses a challenge to the traditional temperature limit of 125°C for high electronic systems, such as those used in down-hole, well-logging and aero-engine applications. The present work aims to develop understanding of how and why attach materials for Si dies degrade/fail under harsh environments by investigating high temperature Au based solders. Au-2wt%Si eutectic melts at < 400°C and offers high temperature stability but high temperature processing and complex manufacturing steps are the major drawbacks. Changes in the die attach material were investigated by isothermal ageing at 35 °C, thermal shock and thermal cycling treatments. Die attach reliability investigated by thermal shock and thermal cycling showed that the bonded area degraded. Nevertheless, most of the samples tested had high bonded area ranging from 92.5 to 97.5%. The failure behaviour of the die attach materials included cracking of die and/or attach material, delamination and voiding. Scanning acoustic microscopy images provided a rapid assessment of delamination and other defects and their location within the package. Microstructural analysis and die shear testing were also carried out, along with the high temperature endurance of a SOI test chip for signal conditioning and processing applications at 25 °C. All functions evaluated have shown stable performance at 25°C for up to 9000 hours.